Формування природничоі компетентності в спеціальній школі - Нагорна Олена; Nahorna Olena; Завітренко Долорес; Zavitrenko Dolores (Видавництво «Код», 2025)
Резюме. У статті визначено основні чинники формування природничої компетентності в спеціальній школі. Окреслено основні завдання та зміст предмету. Корекційна спрямованість передбачає використання спеціальних методів і прийомів навчання для корекції та розвитку школярів із опорою на їхні можливості. Формування природничої компетентності в учнів із інтелектуальними порушеннями змушує враховувати їхні пізнавальні особливості, використовувати інтегровані знання та стимулювати активну практичну діяльність, як-от спостереження, досліди та ін.

Abstract. The knowledge about nature and the surrounding world that students in special schools acquire, compared to the knowledge of students in other types of schools, is limited in terms of the volume of the studied material, simplified in terms of the structure and content of the information offered. The natural and scientific knowledge of students in special schools is mainly formed on the material of such disciplines as natural science and geography. Therefore, it is possible to speak only about the elements of natural science ideas and concepts that are formed in schoolchildren with intellectual disabilities. The content of natural science and geography courses in a special school has a reduced volume of educational information received, the number of special terms and nomenclature of geographical names is reduced. The main task of every special school teacher is to help a child with special educational needs get on the right path, correct their shortcomings as much as possible, do everything so that they do not feel them, and involve them in socially useful activities. To accomplish this task, it is necessary to identify the most effective methods and forms of teaching and improve the entire educational process. The main task of every special school teacher is to help a child with special educational needs get on the right path, correct his shortcomings as much as possible, do everything so that he does not feel them, and involve him in socially useful activities. To accomplish this task, it is necessary to identify the most effective methods and forms of teaching and improve the entire educational process. The acquisition of natural science concepts broadens the students’ worldview, fosters interest and a careful attitude towards nature, develops observation, memory, imagination, speech, and most importantly, logical thinking, the ability to analyze, generalize, classify, establish cause-andeffect relationships and dependencies. The main criterion for the acquisition of natural science content is the formation and development of ideas about the integrity of the natural world, mastering the skill of finding connections between the world of living and inanimate nature, between the world of plants, animals and humans, between the consequences of human activity and nature. The effective assimilation of these connections is facilitated by the use of teaching methods inherent in the natural sciences: conducting observations, experiments, practical work, and demonstrating natural objects.
Formation of natural competence in a special school
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: природнича компетентність; інтелектуальні порушення; спеціальна школа; природничі поняття; корекційна спрямованість